Manoel Barradas: Tractatus Tres Historico-Geographici (1634). A Seventeenth Century Historical and Geographical Account of Tigray, Ethiopia - W. Aregay, Merid (Aethiopica, 1998)
Review ATTENTION: Due to copy-right no online publication is provided